2022
DOI: 10.1038/s41598-022-20397-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel multi epitope-based vaccine against monkeypox virus: vaccinomic approach

Abstract: While mankind is still dealing with the COVID-19 pandemic, a case of monkeypox virus (MPXV) has been reported to the WHO on May 7, 2022. Monkeypox is a viral zoonotic disease that has been a public health threat, particularly in Africa. However, it has recently expanded to other parts of the world, so it may soon become a global issue. Thus, the current work was planned and then designed a multi-epitope vaccine against MPXV utilizing the cell surface-binding protein as a target in order to develop a novel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…Most studies on bioinformatics exploration of peptide-based therapeutics lacked validation of relevant results ( 32 34 ). This may be related to the time- and resource-consuming experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on bioinformatics exploration of peptide-based therapeutics lacked validation of relevant results ( 32 34 ). This may be related to the time- and resource-consuming experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal peptide-based vaccine designed using bio- and immunoinformatics methods should have good immunogenicity and antigenicity, be non-toxic, and non-allergenic. Furthermore, it can induce a robust immune response without causing side effects [87] , [88] . Our results demonstrate that S7M8 is a promising vaccine with good antigenicity, immunogenicity, non-toxicity, and non-sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the S7M8 vaccine is a promising vaccine for SARS-CoV-2 and MPXV prevention. This vaccine has several advantages: (1) the S7M8 vaccine has excellent antigenicity, immunogenicity, non-toxicity, non-sensitization, stability, and solubility; (2) the S7M8 vaccine contained the PADRE helper peptide, TLR2 agonist Pam2Cys, and TLR4 agonist RS-09, which could target APCs such as macrophages to initiate innate immune responses, induce B lymphocytes to secrete high levels of specific antibodies, and activate CD4 + and CD8 + T lymphocytes to produce high levels of cytokines such as IFN-γ and IL-2; (3) in contrast to the original peptide molecules for the prevention of SARS-CoV-2 or MPXV alone, the new peptide molecule S7M8 constructed herein was selected with due reference to the immunodominant antigens selected during the construction of the existing vaccines in the selection of the preparative antigens [88] . This study confirmed that S7M8 provided a protective effect for the host in the case of either SARS-CoV-2 or MPXV infection alone or in the case of co-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another pivotal physical property of the candidate vaccine is solubility. Therefore, the designed vaccine was considered for predicting the solubility property by utilizing a solubility assessing tool for determining the solubility quality to become soluble inside the E. coli host [ 97 ]. Our predicted candidate vaccine passed this parameter.…”
Section: Discussionmentioning
confidence: 99%